Dimension data in Africa : making BEE work - Gaylard, Alison; Mokoaleli-Mokoteli, Thabang ([London] : SAGE, 2016)
In September 2012, IT firm Dimension Data paid out R1.26 billion to the various participants in a broad-based black economic empowerment (BBBEE) deal that the company had signed eight years earlier. When Dimension Data had first embarked on its empowerment journey, legislated BEE in South Africa had been in its fledgling stages and, to a large extent, companies such as Dimension Data had to write their own rules. On the eve of the payout, Jeremy Ord, Dimension Data's executive chairman, reflected on the outcomes of the deal, including the successful growth of the company's Middle East and Africa (MEA) division. He wondered, too, what he would do differently, if he had to do it all over again.
Originally Published in: Gaylard, A., & Mokoaleli-Mokoteli, T. (2014). Dimension Data in Africa: Making BEE Work. WBS-2014-9. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Equal pay for equal work -- South Africa -- Case studies; Discrimination in employment -- South Africa -- Case studies